2012
DOI: 10.1111/j.1748-7692.2011.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Odontocete bycatch and depredation in longline fisheries: A review of available literature and of potential solutions

Abstract: Operational interactions between odontocetes (i.e., toothed whales) and longline gear are a global phenomenon that may threaten the conservation of odontocete populations and the economic viability of longline fisheries. This review attempts to define the issue, summarize the trends and geographical extent of its occurrence over the last half century, explore the potential impact on odontocetes and on fisheries, and describe potential acoustic and physical mitigation solutions. Reports of odontocete bycatch ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 49 publications
2
98
1
1
Order By: Relevance
“…This differs from pelagic longline fishery by the fact that the line is exposed to depredation during all the fishing time (Moreno et al, 2008) and why in ideal conditions the deployment of the DMD occurs when the fish is biting the baited hook. As far as we know our fishing trials were the first carried out in 2007 and in 2008 to test DMD on field for pelagic longline fisheries, while some are currently ongoing (Hamer et al, 2012). Obviously our results show that socks and spiders are not yet ready to be deployed during commercial longline operations to mitigate toothed whale depredation.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…This differs from pelagic longline fishery by the fact that the line is exposed to depredation during all the fishing time (Moreno et al, 2008) and why in ideal conditions the deployment of the DMD occurs when the fish is biting the baited hook. As far as we know our fishing trials were the first carried out in 2007 and in 2008 to test DMD on field for pelagic longline fisheries, while some are currently ongoing (Hamer et al, 2012). Obviously our results show that socks and spiders are not yet ready to be deployed during commercial longline operations to mitigate toothed whale depredation.…”
Section: Discussioncontrasting
confidence: 48%
“…For the first time, our study presents results dedicated to the physical protection of capture to deter predators in pelagic longlining. This depredation mitigation principle is also currently in the development phase in both Tropical South Pacific and Indian oceans, but has not been already trialled (Hamer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that most odontocete species that have been observed depredating are naturally fish‐eaters (Read , Hamer et al . ). For instance, sperm whales depredating in the Southern Ocean are known to feed naturally on toothfish (Yukhov ).…”
Section: Discussionmentioning
confidence: 97%
“…), as well as for other odontocete species that have been documented to depredate worldwide (Clark and Agnew , Hamer et al . , Peterson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The dietary shift could thus be due to the availability of prey items at different times of the year; for example, Neer (2008) reported that pelagic stingrays seasonally target schools of mating squids in the eastern Pacific Ocean. Alternatively, pelagic stingrays could be opportunistically depredating squid bait from pelagic longline sets, which may explain the wide range of estimated contributions by squid in the isotope modeling efforts; such depredation behaviors by odontocete whales have been described previously in longline fisheries (e.g., Hamer, Childerhouse, & Gales, 2012). Pelagic stingrays show a high rate of survival at gear retrieval in the pelagic longline fishery, especially with the circle hooks now required for the US commercial fleet (Kerstetter & Graves, 2006).…”
Section: Stomach Content Analysismentioning
confidence: 91%